2020
DOI: 10.1159/000506809
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Outcomes with Pituitary and Parasellar Disease

Abstract: Over the last 2 decades, advances in the diagnosis and management of pituitary diseases have made it possible to attain an endocrine "cure" in a large proportion of patients. In other words, tumors can be excised or controlled with drugs, mass effects of the lesion on surrounding structures can be solved, and pituitary deficiencies can be substituted with all relevant hormones. While this is considered a satisfactory outcome for health care providers, patients often suffer from an aftermath of prior endocrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Increased duration of opioid use was also associated with a history of anxiety and depression. Compared with the healthy population, patients with pituitary adenomas have higher rates of anxiety and depression than the general population, and these illnesses persist even after surgical intervention 15,16 . Similarly, patients with other anterior skull base neoplasms, such as meningiomas and olfactory neuroblastoma, also have increased rates of comorbid anxiety and depression 17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased duration of opioid use was also associated with a history of anxiety and depression. Compared with the healthy population, patients with pituitary adenomas have higher rates of anxiety and depression than the general population, and these illnesses persist even after surgical intervention 15,16 . Similarly, patients with other anterior skull base neoplasms, such as meningiomas and olfactory neuroblastoma, also have increased rates of comorbid anxiety and depression 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the healthy population, patients with pituitary adenomas have higher rates of anxiety and depression than the general population, and these illnesses persist even after surgical intervention. 15,16 Similarly, patients with other anterior skull base neoplasms, such as meningiomas and olfactory neuroblastoma, also have increased rates of comorbid anxiety and depression. 17,18 This higher prevalence of anxiety and depression in the ESBS population may influence postoperative opioid use.…”
Section: F I G U R Ementioning
confidence: 99%
“…Eight relatives considered the patient to have a very low or low self-esteem (vs. 6 when completed by the patient), while 13 (vs. 12 when fulfilled by the patient) considered the patient to have a high or very high self-esteem (p=0.348). We asked every relative to depict the Stunkard body that would be given by the patient: the median estimated Stunkard body score was 5 [1][2][3][4][5][6][7][8], which was not significantly different compared to the patient's answers (p= 0.171 in comparison with the patient). The same non-significant difference was observed for the IBQ (p=0.549).…”
Section: Resultsmentioning
confidence: 94%
“…In chronic diseases, health-related quality of life has become an increasingly important aspect of patient care [1]. For instance, patients with active as well as controlled acromegaly report an impaired quality of life, linked to the duration of the disease, the necessity of a prolonged medical treatment, a history of radiotherapy or persistent symptoms such as joints complaints [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study in Sweden found that a longer diagnostic delay (defined as the time between the first onset of comorbidity and the diagnosis of acromegaly) led to increased mortality and a greater number of comorbidities ( 9 ). Other than physical health, delayed diagnosis may also have a negative impact on the quality of life and psychosocial functions of daily life ( 10 , 11 ). Therefore, early diagnosis is essential for the future health status of patients with acromegaly ( 12 ).…”
Section: Introductionmentioning
confidence: 99%